STRATEGI HUMAS DALAM SOSIALISASI PROGRAM PPDB (STUDI KASUS DI SMAK SANTO YUSUP) - Laura Ezekiel Tambunan; Durinta Puspasari (STKIP Pesisir Selatan, 2026)
Public relations (PR) plays a strategic role in the successful dissemination of the New Student Admissions Program (PPDB) at private educational institutions. This study aims to analyze the public relations strategy used in the PPDB program dissemination at Santo Yusup High School (SMK Santo Yusup) based on the public relations strategy indicators outlined by Kotler and Keller. This study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, documentation, and questionnaires as supporting data. The data were analyzed inductively to identify patterns and meaning within the information obtained. The results indicate that Santo Yusup High School has implemented all seven public relations strategy indicators. However, the public relations strategy still needs to be optimized, as most people learn about the school through recommendations from individuals already familiar with the school. The conclusions of this study are expected to provide guidance for school public relations practitioners, maximizing the role of alumni through digital communication tools such as WhatsApp or Telegram groups and creating inspirational content with alumni on YouTube or Instagram Reels platforms to broaden their reach to a broader audience.